Strategic Intervention Material: A Competency-Based Instructional Tool for Improving Ninth Graders’ Mathematical Performance - Rubio, Roland (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study was conducted to determine the effectiveness of Strategic Intervention Material (SIM) as a competency-based instructional tool for improving ninth-grade students' mathematical performance. An explanatory sequential mixed-method approach was employed in this study, involving six groups of Grade 9 students who utilized teacher-made strategic intervention materials. The data were gathered from 132 participants using the pretest and posttest. The quantitative data were analyzed using descriptive and inferential statistics such as mean, percentage, standard deviation, independent t-test, and analysis of variance (ANOVA). While the qualitative data obtained from the interview were analyzed through thematic analysis. Findings showed that there was a significant difference between pretest and posttest scores of each group of ninth graders. The result of the ANOVA revealed that there was no significant difference in the pretest and posttest of the six groups of ninth graders, which implies that SIM has the same effect on students’ performance. Students perceived SIM as a valuable material that helps them better understand the lesson and simplify complex topics in math. It was concluded in the study that strategic intervention material helped improve students’ mathematical performance and can be a tool to support students who are struggling in mastering the required competencies. The study supports Sustainable Development Goal 4 by promoting inclusive, equitable, and effective mathematics education through targeted instructional support. Its sustainability impact lies in providing teachers and schools with an adaptable intervention resource that can strengthen remediation programs, improve instructional practices, and sustain learners’ mastery of mathematical competencies over time.
Keywords: Competency-Based Instructional Tool; Grade 9 Students; Learning Experiences; Mathematical Performance; Mixed-Methods Research; Right Triangles; Strategic Intervention Material (SIM); Trigonometric Concepts